GIFT-AI: Damn!.jpg—visual literacy through image-making with generative AI - Källström, Klara (Frontiers in Education, 2025)
This article addresses the growing need for AI literacy by introducing a classroom activity that combines critical theory with hands-on engagement using generative AI image tools. Students were guided through theoretical framing, image selection, AI experimentation, and group analysis. The activity emphasized how prompt design shapes visual outputs and explored the implications of generative systems through selected theoretical frameworks. It created opportunities for students to engage with the aesthetic and epistemological dimensions of AI-generated media. More broadly, he exercise high-lights how image-making can serve as both a critical and creative method for interrogating algorithmic systems across digital art, media education, visual culture, science and technology studies, and critical AI research. The following course framework outlines how the activity was implemented and contextualized within interdisciplinary learning environments.